Irreversibility with quantum trajectories - Wisniacki, Diego Ariel (2005)
Irreversibility is an important issue for many quantum processes. Loschmidt echoes, originally introduced as a way to gauge sensitivity to perturbations in quantum mechanics, have turned out to be a useful tool for its investigation. Following the philosophy supporting this idea, and using quantum trajectories as defined in the causal interpretation of quantum mechanics due to Bohm, we introduce in this paper a more informative alternative measure for irreversibility. The method is applied to the Bunimovich stadium billiard, a paradigmatic example of chaotic system, that constitutes an excellent model for mesoscopic devices. © 2005 The American Physical Society.